Corrosion behavior of X80 pipeline steel in oilfield injection water in Eastern China. Issue 5 (30th August 2021) - Peng, Haoping; Luan, Zhaolin; Liu, Jun; Lei, Yun; Chen, Junxiu; Deng, Song; Su, Xuping
Abstract : Purpose: This paper aims to under the laboratory environment, the corrosion behavior of X80 pipeline steel in oilfield injection water in eastern China was studied by immersion test. Design/methodology/approach: First, the corrosion product film was immersed in oilfield injection water and the effect on the corrosion behavior and the corrosion reaction mechanism were constantly observed during this period. The effect was displayed by potentiodynamic polarization curve and electrochemical impedance spectrums (EIS) measurements. Second, scanning electron microscopy, energy dispersive spectroscopy and X-ray diffraction were used to observe and test the corrosion product film immersed in the oilfield water for 30 days. Findings: The results indicate that the tendency of metal corrosion becomes weaker at an early stage, but strengthened later, which means the corrosion rate is accelerating. Besides, it is indicated by impedance spectroscopy that with the decreasing of the capacitance arc radius, the reaction resistance is reducing in this progress. Meanwhile, the character of Warburg impedance could be found in EIS, which means that the erosional components are more likely to penetrate the product film to reach the matrix. The corrosion product is mainly composed of the inner Fe3 O4 layer and outer shell layer, which contains a large number of calcium carbonate granular deposits. It is this corrosion under fouling that produces severe localized corrosion, forming many etch pits on the metal substrate. Originality/value: The experiment chose the X80 steel, the highest-grade pipeline steel used in China, to conduct the static immersion test in the injection water coming from an oilfield in eastern China. Accordingly, the corrosion mechanism and the effect of corrosion product film on the corrosion of pipeline steel were analyzed and discussed.